METHODS OF THE ORGANIZATIONAL AND TECHNOLOGICAL PLANNING OF STORAGES OF ENTERPRISES OF WHOLESALE - Lina Valeryevna Kazakova (Advanced Engineering Research, 2012)
This article contains information about the availability of trade warehouses, dynamics of regional development defined stages of storage systems, commercial and technological process design, goals and objectives.